Antena Model Delta Loop Untuk Radio Komunikasi Jalur Hf 11 Meter Band - Triyanggono, Wisnu; , Umi Fadlilah, S., M.Eng (2016)
Progress technology for this time more rapidly, especially for technology electronics. The development of technology electronics is very diverse, especially the development of technology of telecommunications in the manufacture of antennas as the beneficiary and radio transmitters to communicate better communication between islands and between countries. Antenna has various kind and shapes to be able to receive and broadcast a signal frequencies. With growing form of an antenna, then it need creativity more to make an antenna that can receive and transmit that can receive and broadcast a signal distance and a little disorder that can reach a distance of radio communication with a nice voice and clear voice. In this research, antenna delta loop in simulation an implementation. The antenna has designed on the frequency of 27 Mhz for HF (High Frequency) and 27,305 Mhz for frequency contact of communication. The materials in use are aluminum form of tubes with thickness big size of aluminum is 1 mm and a diameter of 2,5 cm and thickness of moderate aluminum is 0,7 mm and also diameter of 2,1 cm. Then the shape of triangle and the third site is 3,70 m. The loop antenna using iner of Rg11 in the upper side of antenna trilateral. Based on the results of testing in getting the results for the delta loop antena work on frequency band HF= 27Mhz,VSWR= 1,05. While the sigma4 antena on frequency 27 Mhz, VSWR=1,15. The shape pattern radiation from the antenna is omnidirectional that can be applied as a receiver and transmitter.